Systemic hypoxia increases circulating concentration of apelin in humans - Heinonen, I.; Vuolteenaho, O.; Koskenvuo, J.; Arjamaa, O.; Nikinmaa, M. (High Altitude Medicine & Biology, 2017)
Background: Apelin is a hormone that regulates cardiovascular function, and its concentration is increased by hypoxia based on cell culture and animal studies. As it remains unknown as to whether hypoxia could affect apelin levels in humans, we investigated whether breathing normobaric hypoxic gas mixture increases the circulating apelin concentration in healthy male subjects.